A new species of the genus Boulenophrys (Anura, Megophryidae) from Guizhou, China - Jing Liu; Chao-Bo Feng; Tuo Shen; Shi-Ze Li; Yanlin Cheng; Gang Wei; Bin Wang; Haijun Su (Herpetozoa)
Based on morphological and molecular phylogenetic analyses, a new species of the genus Boulenophrys is described from Yezhong Nature Reserve, Shuicheng County, Guizhou Province, China. Phylogenetic analyses based on the mitochondrial genes 16S rRNA and COI indicate that this new species represents an independent species-level lineage, closely related to B. fanjingmontis, B. qianbeiensis, B. sangzhiensis, and B. spinata. The new species is distinguished from its congeners by a combination of the following characteristics: (1) body size moderate (SVL 41.2–46.2 mm in adult males and 51.8–58.6 mm in adult females); (2) a single small horn-like tubercle at the edge of each upper eyelid; (3) vomerine teeth absent; (4) tongue not notched posteriorly; (5) tympanum distinctly visible, round; (6) toes with rudimentary webbing and narrow lateral fringes; (7) heels overlapping when thighs are positioned at right angles to the body; (8) tibiotarsal articulation reaching the level of the middle of the eye when the leg is stretched forward; (9) a single internal subgular vocal sac in males; (10) in breeding males, the nuptial pads have black nuptial spines on the bases of the first and second fingers.